2019
DOI: 10.1038/s41598-018-37434-5
|View full text |Cite
|
Sign up to set email alerts
|

Mind-wandering, or the allocation of attentional resources, is sleep-driven across childhood

Abstract: Mind-wandering or the spontaneous, uncontrolled changes in the allocation of attention resources (lapses) may cause variability in performance. In childhood, the relationship between the activation state of the brain, such as in attentional performance, and sleep has not been explored in detail. We investigated the role of sleep in attentional performance, and explored the most important parameters of their relationship. We objectively measured momentary lapses of attention of 522 children and correlated them … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 54 publications
3
9
0
Order By: Relevance
“…Our study adds three important contributions to previous literature. First, our study supports the findings of the prior research related to the impact of sleep on mind wandering in children (Spruyt et al, 2019) and has revealed the mechanisms of this association. A recent systematic review of the association between sleep and spontaneous thoughts also suggested the possible underlying mechanisms such as executive function and negative emotion (Cárdenas‐Egúsquiza & Berntsen, 2022).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Our study adds three important contributions to previous literature. First, our study supports the findings of the prior research related to the impact of sleep on mind wandering in children (Spruyt et al, 2019) and has revealed the mechanisms of this association. A recent systematic review of the association between sleep and spontaneous thoughts also suggested the possible underlying mechanisms such as executive function and negative emotion (Cárdenas‐Egúsquiza & Berntsen, 2022).…”
Section: Discussionsupporting
confidence: 92%
“…Recently, mind wandering, regarded as the momentary lapse of attention, has been found to be sleep‐driven across the childhood (Spruyt et al, 2019). Moreover, according to the Local Sleep framework , local sleep (the sleep‐like activity such as slow wave activity and theta waves in the awake brain) intrusions related to sleep loss and poor sleep could predict the occurrences of mind wandering (Andrillon et al, 2019; Jubera‐Garcia et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In many studies, self-reported mind wandering during the SART is also correlated with worse task performance and faster RT (e.g., McVay & Kane, 2011;Kane & McVay, 2012;Thomson, Besner, & Smilek, 2015). These findings seem consistent with frameworks of mind wandering that characterize it in terms of executive control failures (McVay & Kane, 2010) or lapses in vigilance (Spruyt et al, 2019). The link with faster RT is particularly intriguing as a potential real-time, thought probe independent index of mind wandering: with faster RT, the more likely a participant is currently mind wandering.…”
Section: 1: Response Times and Performance Accuracysupporting
confidence: 79%
“…Among the few studies addressing sleep and attention in childhood, Vriend et al [ 27 ] investigated sleep in relation to daytime functioning among children aged 8–12 and found that sleep efficiency was correlated with poorer scores on divided attention. Spruyt et al [ 28 ] examined the role of sleep in the attentional performance of children and adolescents aged 6–18 in a natural setting. They found that across development, various sleep parameters, such as sleep duration, sleep regulation, and sleep midpoint, become increasingly important for attentional performance.…”
Section: Introductionmentioning
confidence: 99%